Zusanli (ST36) Acupoint Injection for Diabetic Peripheral Neuropathy: A Systematic Review of Randomized Controlled Trials - Wang, Li-Qiong (J Altern Complement Med, 2018)
Background: Acupuncture point (acupoint) injection is a common practice in China. Some trials showed that Chinese herbal extracts and/or conventional medication are injected at the Zusanli (ST36) acupoint for the treatment of diabetic peripheral neuropathy (DPN). The study aimed to assess the effectiveness and safety of acupoint injection for DPN at the ST36 by systematically evaluating the evidence published to date. Methods: Six databases were searched for randomized controlled trials (RCTs) of ST36 injection for DPN with primary outcome of pain, global symptom improvement, and quality of life. Methodological quality was assessed by the Cochrane risk of bias (ROB) tool. Data were analyzed using RevMan 5.3. Results: Fourteen RCTs involving 1,071 participants with DPN were included. All RCTs were assessed as unclear or high ROB. Few RCTs adequately reported methodology-related items and needling details according to Consolidated Standards of Reporting Trials (CONSORT) and Standards for Reporting Interventions in Controlled Trials of Acupuncture (STRICTA) statement. Medications injected at ST36 included conventional medications (11 RCTs) and Chinese herbal extracts (3 RCTs). The authors of this study did not perform any meta-analysis due to the heterogeneity of medications used for injections. Two individual RCTs favored ST36 injection in relieving pain compared with intramuscular injection of the same medication. For global symptom measured by Toronto clinical scoring system, one RCT showed that ST36 injection of Fufang Danggui was more effective than intramuscular injection of vitamin B(12), two RCTs demonstrated that ST36 injection of mecobalamin or Danhong with cointervention was superior, while one RCT showed no significant differences between ST36 injection and intramuscular injection of mecobalamin. For improving nerve conduction velocity (NCV), three of four individual RCTs showed that ST36 injection was better than intramuscular or intravenous injection of the same medication, two RCTs favored ST36 injection with cointervention, and one RCT favored ST36 injection without cointervention. Four RCTs reported monitoring adverse events, all of which showed no significant difference between groups. Conclusions: Limited evidence suggests that ST36 injection appears to be safe, and potentially effective in reducing pain score and improving NCV compared with intramuscular injection of the same medication. However, poor methodological and reporting quality reduced confidence in the findings. Rigorously designed and well-reported RCTs evaluating the effectiveness of ST36 injection for DPN are warranted.